"السندات الخضراء آلية لتمويل المشاريع البيئية دراسة تجارب دولية رائدة" - منى قرين; مريم بوزنه; مفيدة بله باسي (جامعة الوادي university of eloued, 2024)
هدفت الدراسة الى التعرف على السندات الخضراء ودورها في تمويل المشاريع الخضراء، وتم استخدم المنهج التحليلي الوصفي، ولقد تم تسليط الدراسة على بعض الدول منها الاجنبية والعربية والمؤسسات والبنوك وطرق تعاملهم بسندات الخضراء، وخلصت الدراسة الى أن تجربة السندات الخضراء وبالرغم من أنها حديثة نسبيا إلا أنها لقت صدى ورواجا كبيرا بين مختلف الدول والهيئات على جميع الأصعدة. The study aimed to identify green bonds and their role in financing green projects .the descriptive analytical approach was used. the study highlighted some countries, including foreign and Arab institutions and banks, and their ways of dealing with green bonds. the study concluded that the experience of green bonds, although it is relatively recent, has received a great resonance and popularity among various countries and bodies at all levels.
Keywords: سندات خضراء- مشاريع بيئية- استثمارات خضراء- طاقة متجددة. green bonds-environmental projects-green investments-renewable energy.